Spontaneous motor tempo contributes to preferred music tempo regardless of music familiarity - Hine, Kyoko; Abe, Koki; Kinzuka, Yuya; Shehata, Mohammad; Hatano, Katsunobu; Matsui, Toshie; Nakauchi, Shigeki (Frontiers in Psychology, 2022)
Music, and listening to music, has occurred throughout human history. However, it remains unclear why people prefer some types of music over others. To understand why we listen to a certain music, previous studies have focused on preferred tempo. These studies have reported that music components (external), as well as participants’ spontaneous motor tempo (SMT; internal), determine tempo preference. In addition, individual familiarity with a piece of music has been suggested to affect the impact of its components on tempo preference. However, the relationships among participants’ SMT, music components, and music familiarity as well as the influence of these variables on tempo preference have not been investigated. Moreover, the music components that contribute to tempo preference and their dependence on familiarity remain unclear. Here, we investigate how SMT, music components, and music familiarity simultaneously regulate tempo preference as well as which music components interact with familiarity to contribute to tempo preference. A total of 23 participants adjusted the tempo of music pieces according to their preferences and rated the familiarity of the music. In addition, they engaged in finger tapping at their preferred tempo. Music components, such as the original tempo and the number of notes, were also analysed. Analysis of the collected data with a linear mixed model showed that the preferred tapping tempo of participants contributed to the preferred music tempo, regardless of music familiarity. In contrast, the contributions of music components differed depending on familiarity. These results suggested that tempo preference could be affected by both movement and memory.